2008
DOI: 10.1152/ajprenal.90385.2008
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective mechanisms of soy protein intake in the obese Zucker rat

Abstract: We previously showed that long-term consumption of a soy protein diet (SoyP) reduces renal damage in obese Zucker (ObeseZ) rats by restoring urinary NO 2 and NO 3 excretion (UNO2/NO3V), suggesting that nitric oxide (NO) deficiency may contribute to the renal progression observed in this model. In addition, there is compelling evidence that hyperleptinemia produced deleterious effects on the kidney through its interaction with the short leptin receptor (ObRa). This study was designed to evaluate the contributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
(67 reference statements)
1
11
0
Order By: Relevance
“…Notably, feeding an isoflavone enriched diet to rats for only 4-6 months has marginal benefits for endothelial function (Douglas et al, 2006), suggesting that isoflavone supplements may only affect endothelial function in aged animals with existing CVD (Trujillo et al, 2005(Trujillo et al, , 2008. Consistent with the reported vasodilatory actions of genistein and dehydroequol in humans (Walker et al, 2001;Chin-Dusting et al, 2004), we have shown that isoflavones evoke rapid endothelium-dependent and -independent relaxation of preconstricted arterial rings (Joy et al, 2006).…”
Section: Isoflavones As Dietary Modulators Of Cardiovascular Functionsupporting
confidence: 57%
“…Notably, feeding an isoflavone enriched diet to rats for only 4-6 months has marginal benefits for endothelial function (Douglas et al, 2006), suggesting that isoflavone supplements may only affect endothelial function in aged animals with existing CVD (Trujillo et al, 2005(Trujillo et al, , 2008. Consistent with the reported vasodilatory actions of genistein and dehydroequol in humans (Walker et al, 2001;Chin-Dusting et al, 2004), we have shown that isoflavones evoke rapid endothelium-dependent and -independent relaxation of preconstricted arterial rings (Joy et al, 2006).…”
Section: Isoflavones As Dietary Modulators Of Cardiovascular Functionsupporting
confidence: 57%
“…Enhanced ROS formation during hyperglycemia could be one factor for elevation in TGF-β1, since antioxidants inhibit glucose-induced upregulation of TGF-β1 [33]. Significant reduction in TGF-β1 expression by soy protein has been shown in another model of IR [34].…”
Section: Discussionmentioning
confidence: 99%
“…There is abundant experimental evidence, and to a lesser degree, clinical evidence, demonstrating that the amount and type of dietary protein may influence kidney function (11,12,33,39,47,49). Despite some controversy, there is a generalized belief that low-protein diets are beneficial in the treatment of patients with CKD and can reduce the progression of kidney disease (3,33,39).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been claimed that vegetable protein is beneficial for individuals with CKD as it can help improve renal blood flow perfusion and reduce inflammation (12). Indeed, vegetable proteins like soy protein increase the production of nitric oxide, promoting normal renal function in obese rats (49). Additionally, soy protein preserves glomerular filtration rate in rats with chronic renal failure in clear association with the lower production of metabolic acid evaluated by the urine net acid excretion and kidney acid content (57).…”
Section: Discussionmentioning
confidence: 99%